The Impact of Project Manager’s Skills and Age on Project Success - Elmezain, Maryam (2021)
Goal: This study seeks to examine project success in relation to project managers’ factors. Pertaining to research questions, we highlighted: “do project manager’s technical, conceptual, political and human skills are significantly related to project success?, and does project manager’s age play a significant role in achieving project success? Design / Methodology / Approach: This research employed a quantitative research method using survey questionnaires to collect data from 400 project managers working in five well-known construction companies in Cairo, Egypt. Descriptive statistics using Relative Importance Index (RII) were employed to rank the dimensions of project manager’s skills: conceptual, technical, human and political skills; and project success dimensions: cost, schedule and quality. Multiple regression analysis was used to identify the impact of project managers’ skills on project success while simple linear regression was used to examine the relationship between project manager’s age and project success Results: The results of RII revealed that project managers maintain a competitive level of technical, conceptual, political and human skills, and emphasize on specific aspects of cost, schedule, and quality dimensions of project success. The regression analysis revealed that 49.2% of the explained variation in project success can be accounted for technical, political, human and conceptual skills at coefficient of determination values of 0.611, 0.506, 0.431 and 0.407 respectively while the project manager’s age had no association with project success with a P value 0.694 at alpha level of 0.05. Limitations of the investigation: Generalizing research findings might be challenged because sample size was randomly selected due lack of identifying the exact size target population. Practical implications: The managerial implication of this study lies in the need for construction companies not to consider project manager’s age as a significant factor for project success, instead they need to ensure that project managers possess a competitive level of conceptual, technical, political and human skills. Originality / Value: Pertaining to contribution to academia, this research argues that project success subject to a set of comprehensive set of project managerial skills namely conceptual, technical, political and human. Further, it is essential to distinguish between project manager’s age and experience and not to consider project manager’s age as a determinant of a project success.